Municipal interventions against inequalities in health: The view of their managers. Issue 6 (August 2014) - Diez, Elia; Morrison, Joana; Pons-Vigués, Mariona; Borrell, Carme; Corman, Diana; Burström, Bo; Dominguez-Berjón, Felicitas; Gandarillas, Ana; Hoffmann, Rasmus; Santana, Paula; Camprubí, Lluís
Background: European city councils are increasingly developing interventions against health inequalities. There is little knowledge about how they are perceived. This study describes and analyses good practices and challenges for local interventions on inequalities in health through the narratives of European city managers. Methods : A qualitative study was conducted. Each participating city (Amsterdam, Barcelona, Cluj-Napoca, Helsinki, Lisbon, London, Madrid, Rotterdam) selected interventions following these criteria: at least 6 months of implementation; an evaluation performed or foreseen; the reduction of health inequalities among their objectives, and only one of the interventions selected could be based on health care. Managers of these local interventions were interviewed following an outline. Eleven individual in-depth interviews describing nine local interventions were obtained. A thematic content analysis was performed. Results : One or more local interventions against health inequalities were identified in each city. Most relied on quantitative data and were linked to national strategies. Few interventions addressed socio-economic determinants. Health care, employment and education were the main determinants addressed. With variable depth, evidence-base, participation and intersectorality were regular components of the interventions. Half of them targeted the city and half some deprived neighbourhoods. Few interventions had been evaluated. Scarcity of funding and sustainability of the projects were the main perceived barriers by the managers. Conclusions : City intervention managers were familiar with health inequalities and concepts as intersectorality, participation and evidence-based action, but others such as socioeconomic aims, gradient approach, evaluation and sustainability were not so widely applied. Managers' capacities and political leadership in governance for health should be reinforced.